PENGARUH BEBERAPA FAKTOR SECARA PARSIAL DAN SIMULTAN TERHADAP PERMINTAAN TRANSPORTASI ONLINE GOCAR DAN GRABCAR DI KOTA MATARAM - ROHANI, ROHANI; HASYIM, HASYIM; SUAEB, SUAEB (Universitas Mahasaraswati K. Mataram, 2024)
Technological developments that occur in the global world today have resulted in changes in the choice of transportation modes in Indonesia, especially in the city of Mataram. Apart from that, the government's inability to provide public transportation has caused people to switch to other transportation that makes it easier and shortens travel time, namely online transportation. Application-based or online transportation services are currently one of the people's choices for traveling. One of the largest and most popular types of online transportation services currently that uses an online system is Gojek and Grab.This study was conducted to determine the factors that influence the demand for online transportation, namely GoCar and GrabCar. The analysis was carried out using multiple linear regression to determine the influence of the variables cost, distance, income, number of family members, ownership of private vehicl and waiting time.From the results of the analysis, it was found that demand for GoCar was partially influenced by cost, distance and income factors. Meanwhile, demand for GrabCar is partially influenced by cost and distance factors. Simultaneously, demand for GoCar and GrabCar is influenced by the factors cost, distance, income, number of family members, private vehicle ownership and waiting time by 81.4%, likewise demand for GoCar and GrabCar is partially influenced by these six factors.